Integrative taxonomy reveals too extensive lumping and a new species in the moss genus Amphidium (Bryophyta). Issue 5 (3rd September 2017) - Sim-Sim, Manuela; Afonina, Olga M.; Almeida, Tereza; Désamoré, Aurélie; Laenen, Benjamin; Garcia, César Augusto; González-Mancebo, Juana M.; Stech, Michael
Abstract : An integrative taxonomic approach, including molecular phylogenetic reconstructions based on plastid rps4-trnF and nuclear ITS sequences, statistical analysis of morphological-anatomical characters, and classical taxonomy, indicates that the reduction of 13 Amphidium species to three in a recent morphological revision represents a case of too extensive lumping. Instead, six Amphidium species can be distinguished based on molecular and morphological data, the widespread Amphidium lapponicum, A. mougeotii, and A. tortuosum, as well as the Macaronesian endemic A. curvipes, the North American endemic A. californicum, and a newly discovered species from Central Asia (southern Siberia and northern Mongolia), A. asiaticum sp. nov. Diagnostic morphological characters for all six species are discussed. The present data confirm that species diversity of Amphidium is highest in the Holarctic, where all six species occur.